Efeito farmacológico das frações hexânica, clorofórmica e metanólica do óleo essencial da Alpinia zerumbet na reatividade vascular in vitro e nos parâmetros cardiovasculares in vivo - Cunha, Gilmara Holanda da (2012)
The Alpinia zerumbet is a plant of the family Zingiberaceae, popularly called "colônia" in Northeastern Brazil. It is used for medicinal purposes to treat hypertension and has been studied in relation to its pharmacological properties. This study aimed to analyze the pharmacological effect of hexanic (HFEOAz), chloroformic (CFEOAz), and methanolic (MFEOAz) fractions of the essential oil of Alpinia zerumbet (EOAz) in the vascular reactivity in vitro and cardiovascular parameters in vivo. The research project was approved by the Ethics Committee on Animal Research, of the Federal University of Ceará, under protocol numbers 55/10 and 18/2011, according to the standards of good laboratory practice involving the use of experimental animals. For all experiments male Wistar rats were used. Experiments of vascular reactivity were conducted in organ bath, with preparations of isolated rat aorta with intact endothelium and desnuded, kept in carbogen and Krebs-Henseleit solution with a concentration in mmol/L: NaCl: 118,0; KCl: 4,7; KH2PO4: 1,2; MgSO4.7H2O; 1,2; NaHCO3: 15,0; CaCl2: 2,5 e Glicose: 5,5. Was observed variation in isometric tension and used different specific inhibitors to analyze the mechanism of action of the vasodilator effect. We analyzed blood pressure indirectly by tail plethysmography in rats submitted to chronic hypertension by inhibition of nitric oxide by the administration of L-NAME, obtaining the systolic, diastolic and mean blood pressure, heart rate, beyond variation in body weight. It was found that the EOAz, HFEOAz, CFEOAz MFEOAz induced relaxation of aortic rings pre-contracted with Phenylephrine (1 mol/L), of dose-dependent manner, with the smallest of the EC50 MFEOAz (150.45 mg/mL). The administration by gavage of 100 mg/kg EOAz, HFEOAz, CFEOAz MFEOAz reduced blood pressure in hypertensive rats by the model of chronic inhibition of nitric oxide, an effect that was greater than the negative control with distilled water and less than the positive controls with Captopril and Nifedipine. The MFEOAz (0.1 - 3000 µg/mL) concentration dependently relaxed Phenylephrine (1 mol/L) and KCl (80 mmol/L) contracted rings with intact or denuded endothelium. Studies of calcium mobilization showed that FMOEAz inhibits the influx of Ca2+ from the extracellular environment and interferes with the contraction-induced Ca2+ release from intracellular stocks by Phenylephrine (1 mol/L) or Caffeine (30 mmol/L). The 4-aminopyridine (1 mmol/L) and Iberiotoxina (30 nmol/L) increased the EC50 of MFEOAz but do not interfere in its final vasodilator effect. The pre-incubation with L-NAME (100 mol/L), ODQ (10 mol/L), Indomethacin (10 mol/L), Atropine (1 mol/L), Catalase (500 U/mL), SOD (300 U/mL), Wortmannin (0.5 mol/L), Tetraethylammonium (10 mmol/L), Apamin (1 mol/L); Caribdotoxin (15 nmol/L) and Glibenclamide (10 mol/L) did not interfere with the relaxation induced by MFEOAz. It was concluded that the EOAz, HFEOAz, CFEOAz and MFEOAz have hypotensive effect in vivo and vasodilator effect in vitro, and that the mechanism of action of MFEOAz probably involves the antagonism of calcium channels voltage-dependent, the calcium channel operated by receptor, also interfering in the release of calcium from intracellular stores.